Global research trends and frontiers in ferroptosis in hepatocellular carcinoma: a bibliometric and visualization study - Ning, Lin; Chen, Di; Han, Jie; Xie, Guanyue; Sun, Jianguang (Frontiers in Oncology, 2024)
BackgroundSince the emergence of the hot topic of “ferroptosis,” numerous studies have explored its role in hepatocellular carcinoma (HCC), revealing its significance in the disease’s pathogenesis, progression, and treatment. However, there remains a significant gap in the quantitative analysis of ferroptosis in HCC. Therefore, this study aims to comprehensively assess the research progress and evolution in this field through bibliometric and citation analysis.MethodOn June 27, 2024, the author conducted a literature search, extracting relevant publications from the Web of Science Core Collection (WOSCC) Science Citation Index Expanded (SCIE) spanning from January 2010 to December 2023. Subsequently, the compiled documents were subjected to bibliometric evaluation and analysis using visualization tools such as R package “bibliometrix”, CiteSpace and VOSviewer.ResultThe search yielded 576 papers by 3,925 authors, encompassing contributions from 34 countries and 685 institutions, published across 250 journals, including 25,889 co-cited references from 2,600 journals. Notably, China leads with a significant publication count of 481 articles (accounting for 83.5%) and demonstrates the strongest collaboration with the United States. The multifaceted role of ferroptosis in hepatocellular carcinoma (HCC) has garnered considerable attention. In recent years, research into disease prognosis, the tumor microenvironment, and targeted therapies involving immunology has become key themes and emerging frontiers in this field.ConclusionThis study meticulously compiled and analyzed the current discourse and emerging perspectives on ferroptosis in HCC. Identifying research trends and hotspots offers valuable guidance for future investigations and provides a basis for the development of novel therapeutic strategies to improve HCC prognosis and treatment outcomes.